A Modular Programming Approach for IoTBased Wireless Sensor Networks - Gaur, Shashank (2015)
Poster presented in 12th European Conference on Wireless Sensor Network (EWSN 2015). 9 to 11, Feb, 2015. Porto, Portugal.